Photoremovable chiral auxiliary - Kammath, Viju Balachandran; Sebej, Peter; Slanina, Tomáš; Kříž, Zdeněk; Klán, Petr (Photochemical & photobiological sciences, 2012)
A new concept of a photoremovable chiral auxiliary (PCA), based on the chiral benzoin chromophore, is introduced. This moiety can control the asymmetric formation of a Diels-Alder adduct, and then be removed in a subsequent photochemical step in high chemical and quantum yields. Selective formation of the products at up to 96% ee was observed in the presence of a Lewis acid catalyst in the case of a 2-methoxybenzoinyl chiral auxiliary.
Keywords: benzoin; fotolýza; Models, Molecular; Molecular Structure; molekulární struktura; molekulární modely; Photolysis; Benzoin